Delineation of joint molecule resolution pathways in meiosis identifies a crossover-specific resolvase - Zakharyevich, Kseniya (2012)
At the final step of homologous recombination, Holliday Junction-containing joint molecules (JMs) are resolved to form crossover or noncrossover products. The enzymes responsible for JM resolution in vivo remain uncertain, but three distinct endonucleases capable of resolving JMs in vitro have been identified: Mus81-Mms4(EME1), Slx1–Slx4(BTBD12) and Yen1(GEN1). Using physical monitoring of recombination during budding yeast meiosis, we show that all three endonucleases are capable of promoting JM resolution in vivo. However, in mms4 slx4 yen1 triple mutants, JM resolution and crossing-over occur efficiently. Paradoxically, crossing-over in this background is strongly dependent on the Blooms helicase ortholog, Sgs1, a component of a well-characterized anti-crossover activity. Sgs1-dependent crossing-over, but not JM resolution per se, also requires XPG-family nuclease, Exo1, and the MutLγ complex, Mlh1–Mlh3. Thus, Sgs1, Exo1 and MutLγ together define a previously undescribed meiotic JM resolution pathway that produces the majority of crossovers in budding yeast and, by inference, in mammals.